Determination of the platinum concentration of a Pt/silica nanocomposite decorated with ultra small Pt nanoparticles using single particle inductively coupled plasma mass spectrometry. Issue 5 (6th April 2017) - Sápi, András; Kéri, Albert; Kálomista, Ildikó; Dobó, Dorina G.; Ákos Szamosvölgyi,; Juhász, Koppány L.; Ákos Kukovecz,; Kónya, Zoltán; Galbács, Gábor
Abstract : The accurate load concentration of ultra small nanoparticles in a Pt/SiO2 nanocomposite is determined by the novel spICP-MS analytical method. Abstract : In this study, the performance of five analytical techniques applicable to the determination of the load concentration of ultra small nanoparticles in a Pt/SiO2 nanocomposite was critically evaluated. Four of the techniques (SEM-EDS, TEM imaging, XPS and solution-mode ICP-MS) are often used for the characterization of nanoparticles, whereas single particle ICP-MS (spICP-MS) is an upcoming, novel methodology. After experimentally testing and discussing the pros and cons of each analytical technique, it was found that spICP-MS is one of the most accurate, precise and practical techniques for the analysis of nanocomposites. This technique works directly with dispersions, the measurement only takes a few minutes, it gives highly reliable results, largely free from interference from precursor residues and can also provide additional information about the particles. Although the individual measurement of ultra small nanoparticles is not yet possible by spICP-MS, the cumulative signal from such load particles in a nanocomposite allows the accurate determination of the load concentration. The spICP-MS result was concordant with the result obtained by TEM imaging, whereas SEM-EDS, XPS and solution-mode ICP-MS strongly overestimated the concentration.